Food systems for healthier diets in Bangladesh: Towards a research agenda - de Brauw, Alan; Waid, Jillian; Meisner, Craig A.; Akter, Fahmida; Khan, Bushra Ferdous; Alam, Nazmul (International Food Policy Research Institute, 2019)
The national food system of Bangladesh has made substantial progress since experiencing famine in 1974, soon after independence. After the famine, the government placed a strong emphasis on policies required to attain grain self-sufficiency; since attaining self-sufficiency, the production system, policies related to it, and resulting diets have begun to diversify. Nonetheless, undernutrition remains a problem, and fruit and vegetable consumption are inadequate for most people relative to international recommendations. Moreover, as the food system has begun to transition towards a modern one, challenges related to food safety and perceived food adulteration have begun to rise. Further, increased processed food intakes are potentially associated with existing rising overweight and obesity status. Both government interventions and innovations are needed to help shift the national food system to improve nutrient-dense food availability, particularly among the poor, and to limit the increase in processed food consumption.